Growth of banking credit in indonesia influence on economic growth in the pandemic - Nagian Toni; Thomas Sumarsan Goh (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2022)
The economic downturn in Indonesia has been experienced since Covid-19. Impact on various sectors of the world economy. Significant changes experienced by Indonesian citizens. Covid-19 pandemic is a challenge for the business world, including the banking financial services industry. This caused the state financial system to be shaken until 2021. This study aimed to examine how the development of credit at Bank Rakyat Indonesia (BRI) during pandemic. BRI in carrying out its function as an intermediary banking institution, such as collecting funds and distributing funds to run its duties and functions amid the Covid-19 pandemic. This research is qualitative research with a phenomenological method approach since the research was conducted in a conditionsof social phenomena specifically in Gegesik sub-district, Cirebon Regency, with four customers as primary subjects, two marketing and one teller as secondary subjects. The discussion is described in the form of descriptive analysis. The results of the study show that the Covid-19 pandemic has had a major impact on the decline in the world economy for micro and macro business actors in Indonesia, including the MSME sector. To overcome this, the Government seeks to overcome these problems by issuing the People's Business Credit (KUR) program. There is a change in the 2022 period when the monthly installments are smooth. However this medium growth rate is not enough to answer the problem of disease and mission. To overcome this, optimism is needed that the MSME sector can recover in 2022 and of course it is supported by the right policies.